Reduced glucose‐induced insulin secretion in low‐protein‐fed rats is associated with altered pancreatic islets redox status. Issue 1 (3rd May 2017) - Cappelli, Ana Paula G.; Zoppi, Claudio C.; Silveira, Leonardo R.; Batista, Thiago M.; Paula, Flávia M.; da Silva, Priscilla M. R.; Rafacho, Alex; Barbosa‐Sampaio, Helena C.; Boschero, Antonio C.; Carneiro, Everardo M.
Abstract : In the present study, we investigated the relationship between early life protein malnutrition‐induced redox imbalance, and reduced glucose‐stimulated insulin secretion. After weaning, male Wistar rats were submitted to a normal‐protein‐diet (17%‐protein, NP) or to a low‐protein‐diet (6%‐protein, LP) for 60 days. Pancreatic islets were isolated and hydrogen peroxide (H2 O2 ), oxidized (GSSG) and reduced (GSH) glutathione content, CuZn‐superoxide dismutase (SOD1), glutathione peroxidase (GPx1) and catalase (CAT) gene expression, as well as enzymatic antioxidant activities were quantified. Islets that were pre‐incubated with H2 O2 and/or N‐acetylcysteine, were subsequently incubated with glucose for insulin secretion measurement. Protein malnutrition increased CAT mRNA content by 100%. LP group SOD1 and CAT activities were 50% increased and reduced, respectively. H2 O2 production was more than 50% increased whereas GSH/GSSG ratio was near 60% lower in LP group. Insulin secretion was, in most conditions, approximately 50% lower in LP rat islets. When islets were pre‐incubated with H2 O2 (100 μM), and incubated with glucose (33 mM), LP rats showed significant decrease of insulin secretion. This effect was attenuated when LP islets were exposed to N‐acetylcysteine. Abstract : Our data suggest that short‐term early life protein malnourishment induces reduction in redox GIIS signaling only at extreme oxidant challenges, elicited here by high H2 O2 pre‐incubation followed by elevated glucose concentration incubation, probably due to lower antioxidant scavenging capacity.